Preparation of electron buffer layer with crystalline ZnO nanoparticles in inverted organic photovoltaic cells. (June 2017) - Lee, Donghwan; Kang, Taeho; Choi, Yoon-Young; Oh, Seong-Geun
Abstract: Zinc oxide (ZnO) nanoparticles synthesized through sol-gel method were used to fabricate the electron buffer layer in inverted organic photovoltaic cells (OPVs) after thermal treatment. To investigate the effect of thermal treatment on the formation of crystalline ZnO nanoparticles, the amorphous ZnO nanoparticles were treated via hydrothermal method. The crystalline phase of ZnO with well-ordered structure could be obtained when the amorphous phase of ZnO was processed under hydrothermal treatment at 170 °C. The crystalline structure of ZnO thin film in inverted organic solar cell could be obtained under relatively low annealing temperature by using thermally treated ZnO nanoparticles. The OPVs fabricated by using crystalline ZnO nanoparticles for electron buffer layer exhibited higher efficiency than the conventional ZnO nanoparticles. The best power conversion efficiency (PCE) was achieved for 7.16% through the ZnO film using the crystalline ZnO nanoparticles. The proposed method to prepared ZnO nanoparticles (NPs) could effectively reduce energy consumption during the fabrication of OPVs, which would greatly contribute to advantages such as lower manufacturing costs, higher productivity and application on flexible substrates. Highlights: Crystalline ZnO nanoparticles were prepared through hydrothermal process with amorphous nanoparticles. Electron transport layer in inverted OPV was manufactured with crystalline ZnO nanoparticles. PCE of OPV was increased by using crystalline ZnO nanoparticles. High temperature annealing process for OPV device can be circumvented by this method.